2010
DOI: 10.14295/bds.2005.v8i3.327
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of the topical use of propolis in recurrent minor aphthous ulceration

Abstract: Our purpose was to evaluate the therapeutic effects of a natural product (propolis) on recurrent aphthous ulceration (RAU) of the minor type regarding the number of lesions, their duration and frequency of recurrence. Seventy patients with RAU composed the study group who were examined according to pre-established criteria. Forty patients presenting with RAU (mean age 38.5 years; 25 women and 15 men) were selected and medicated during the recurrence of their lesions using a purified propolis solution in a 5%pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 9 publications
1
4
0
10
Order By: Relevance
“…Bowel disorders, either due to nutritional deficits or gastrointestinal pathology, have also been referred to as triggering causes in different works. 1,25,28,44 Hormonal changes were the least common predisposing factor (7 %), which is consistent with reports by Axéll et al 40 (8 %) and Lotufo et al 41 (2.5 %). In a systematic review carried out by McCartan and Sullivan 45 , no relationship was found between RAS onset and menstrual cycle, pregnancy, menopause or hormone replacement therapy; conversely, some authors 3,7,27,39 have given much higher relevance to this factor.…”
Section: In China Orsupporting
confidence: 89%
See 2 more Smart Citations
“…Bowel disorders, either due to nutritional deficits or gastrointestinal pathology, have also been referred to as triggering causes in different works. 1,25,28,44 Hormonal changes were the least common predisposing factor (7 %), which is consistent with reports by Axéll et al 40 (8 %) and Lotufo et al 41 (2.5 %). In a systematic review carried out by McCartan and Sullivan 45 , no relationship was found between RAS onset and menstrual cycle, pregnancy, menopause or hormone replacement therapy; conversely, some authors 3,7,27,39 have given much higher relevance to this factor.…”
Section: In China Orsupporting
confidence: 89%
“…Stress as a relevant predisposing factor for RAS has been widely suggested in investigations that consider oral mucosa as a target organ in certain emotional disorders. 2,3,19,25,30,32,38,41 The disparity of results around this factor probably lies in the studied sample sizes, type of population and in differences in the investigations' methodological design.…”
Section: In China Ormentioning
confidence: 99%
See 1 more Smart Citation
“…duração e frequência de recidivas. Concluiu-se que a própolis é bastante eficaz no tratamento desta alteração (Lotufo et al, 2005).…”
Section: Efeito Da Própolis Sobre Ulcerações Aftosas Recorrentesunclassified
“…It has a bactericide, antimicrobial [5], antioxidant [6], antifungal [7], healing, anti-inflammatory [8], anti-cancerous, anti-HIV [9] and anti-carious biological function [10].…”
Section: Introductionmentioning
confidence: 99%